INCLUSIVE EDUCATION – AN IMPORTANT STEP TOWARDS EQUAL OPPORTUNITIES (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article highlights the concept of inclusive education, its essence, and its role in the modern education system. The main goal of inclusive education is analyzed as creating broad and accessible educational conditions for all children, regardless of their physical, intellectual, or psychological abilities. The article discusses the advantages of inclusive education, its role in ensuring social equality in society, as well as the challenges encountered in its implementation and possible solutions. The research findings show that the development of inclusive education can improve the quality of education and strengthen social cohesion.